2021
DOI: 10.14740/wjon1418
|View full text |Cite
|
Sign up to set email alerts
|

Management of Male Breast Cancer: The Journey so Far and Future Directions

Abstract: Male breast cancer is now shown to be a unique entity and should be considered as a distinct disease. Given the relatively smaller number of cases, randomized controlled trials for treatment are extremely limited and majority of practices are derived from female breast cancer studies. This paper reviews available literature on surgical, radiation, and systemic therapies for male breast cancer, and discusses current practice recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…Breast cancer is the most common type of cancer and the one that causes the highest number of deaths in women worldwide [ 1 ]. In contrast, this type of cancer is rare in men [ 2 ], accounting for approximately 1% of all breast cancer diagnoses in the world [ 3 ]. The management of male breast cancer is based on studies conducted on women or female animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is the most common type of cancer and the one that causes the highest number of deaths in women worldwide [ 1 ]. In contrast, this type of cancer is rare in men [ 2 ], accounting for approximately 1% of all breast cancer diagnoses in the world [ 3 ]. The management of male breast cancer is based on studies conducted on women or female animal models.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that these differences may be related to distinct biological processes in men and women influencing tumorigenesis, mainly hormonal variations related to androgens, estrogens, and progestins. Genomic differences in breast cancer cases have also been evidenced between men and women; for example, in ER- and PR-positive male breast cancers mutations that are common in ER- and PR-positive female breast cancer cases (e.g., PIK3CA and TP53) are less likely to be identified in men [ 3 , 8 ]. Molecular studies show that gene expression patterns and the susceptibility to develop breast cancer are sex-dependent in mice (BALB/c and C57BL/6) [ 9 ], supporting the idea that the biology of breast cancer may be different in men and women.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, epidemiology was reviewed in pancreatic cancer by Rawala et al [ 1 ], in prostate cancer by Cassell et al [ 2 ] and Rawala [ 3 ], in renal cell carcinoma by Padala et al [ 4 ], and in malignant melanoma by Naik [ 5 ]. Review articles also provide an opportunity to learn about the latest updates and summaries on relatively rare conditions such as male breast cancer [ 6 ], urothelial carcinoma [ 7 ], mucoepidermoid carcinoma [ 8 ], retroperitoneal liposarcoma [ 9 ], and even on hemophagocytic lymphohistiocytosis, a relatively rare side effect of immune checkpoint inhibitor therapy [ 10 ]. There were several review articles on topics that apply to all types of cancer, such as infections in hospitalized cancer patients [ 11 ], genetic polymorphisms [ 12 ], tumor dormancy [ 13 ], and unstable psychiatric disorder [ 14 ].…”
mentioning
confidence: 99%